Phenotypic Characterization of Multidrug Resistant Klebsiella Spp. Isolated from Pediatric Patients - Asghar, Azka; Hashmi, Atika; Khalid, Ayesha; Waqas Ali; Ashiq, Aqsa; Khan, Abeeha Shahzad (BioScientific Review, 2025)
infections are difficult to eradicate due to the presence of β-lactamases. The current study aimed to identify multidrug resistant isolates in children due to their high prevalence in Lahore, Pakistan. Methodology. In this study, 150 samples of blood, urine, pus, ascitic fluid, pleural fluid, Bronchoalveolar lavage (BAL), and CSF were collected from patients admitted in the University of Child Health Sciences, The Children’s Hospital, Lahore from November 2021 to April 2022. Then, different microbiological techniques including culturing, Gram staining, identification of different species by using API, antibiotic susceptibility testing as well as molecular techniques including PCR, were used to identify MDR Klebsiella spp. positive samples. Results. Out of the 150 samples, 58 were found positive for Klebsiella spp. while 92 were negative for Klebsiella spp. Among these 58 strains, 48 came from urine samples, 8 from pus samples, and 2 from blood samples. Furthermore, 34 were collected from male and 24 from female patients. The age group of the sampled children was 6 to 10 years. Afterwards, these 58 isolates were screened for extended spectrum β-lactamase (ESBL), metallo β-lactamase (MBL) and AmpC. It was found that out of these 58 isolates, 12 were ESBL positive (20.68%), 11 were MBL positive (18.9%) and 20 were AmpC positive (34.48%). Among β-lactamase genes, NDM -1 (72.7 %), SHV (41.6%), TEM (8.3%) and CTX-M (25%) were detected. Conclusion. The study concluded that the rate of MDR Klebsiella infection is high in children and it may be complicated for the clinicians to treat them.